Integrated management of cercospora leaf spots and yellow mosaic of urdbean (Vigna mungo) - DUBEY, S C; SINGH, BIRENDRA (The Indian Journal of Agricultural Sciences, 2011)
A study was conducted during rainy season of 2003 and 2004 for the management of cercospora leaf spots (C cailescens and Pseudocercospora crcieritn)and yellow mosaic (Mungbean yellow mosaic virus) of urdbean ( I vigna mungo (L.) Hepper) by integrating insecticides; fungicides and fungal bioagent as seed treatment and foliar spray. Thc combination of seed soaking in 0.1% irnidacloprid 17.836SL for 2hr and dry seed treatment with carbendazim 50LVP + tetra methyl thiuram disulphide (TMTD) 75WP ( 1 : l ) @; &!kg seed followed by foliar sprays of 0.02% imidacloprid and 0.05?6 carbendazim at 30 and 45 days after sowing respectively was the best treatment to minimize intensity of cercospora leaf spots (4.3%) and yellow mosaic (MYMV) (9.5%) resulting in maximum grain yield (954.2 kg/ha). Seed germination percentage of this interaction was also significantly superior over the control. Prior to field experiment the biological compatibility of imidacloprid and thiamethoxam with carbendazim + TMTD for seed treatment was tested viitro and their combination supported maximum seedling vigour.